Effect of Low Temperature Storage on Sensitivity to Antibiotics of Polyresistant Escherichia coli Strains - Peretyatko, Olena; Gurina, Tetiana; Yagnuk , Yulya; Krestetska, Svitlana; Sklyar, Nadia; Yagnuk Аndrii; Pakhomov, Oleksandr; Bolshakova, Halyna (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):309